Use of Hec-Ras Software to Analyze Floods in Joyoakan Urban Village, Surakarta City, Central Java - Sigit Riswanto; Mahdika Putra Nanda (JACEE (Journal of Advanced Civil and Environmental Engineering), 2023)
One of the natural phenomena that threaten the existence of human life in several regions in Indonesia every time the rainy season begins is flooding, one of which occurs in the Joyoakan sub-district in Surakarta City. Topographically, it is in a hollow area (under the main road), making it easier for water to enter the area. This is what makes the Premulung and Kaliwingko rivers unable to accommodate rainwater discharge and additional rainwater shipments from the Boyolali and Sukoharjo areas. The purpose of this study is to determine how much volume of inundation in the drainage canal can be reduced in the Joyoakan area and the appropriate efforts to deal with the inundation that occurs. The method used is descriptive research, to provide an overview of the variables studied and modeling using the HEC-RAS software. The result of the calculation is that the potential for inundation that can be reduced by the drainage channel is at the Q5 return period of 6,842.577 m3, the Q10 return period is 6,962.517 m3, and at the Q25 return period is 7,100.448 m3, while the results from the channel dimension modeling analysis, there are still puddles at several points, the right alternative in overcoming inundation is the need to revitalize the drainage channels by increasing the capacity of the drainage dimensions from the current size and improving the base slope of each channel and installing pumps as a means of control in accelerating water discharge